2004
DOI: 10.1002/ptr.1349
|View full text |Cite
|
Sign up to set email alerts
|

Effect of garlic oil on ethanol induced gastric ulcers in rats

Abstract: Garlic oil was evaluated for gastroprotective activity against ethanol induced ulcers. Reactive oxygen species are involved in the pathogenesis of these ulcers. The possible involvement of garlic oil in restraining the oxidation process produced in gastric tissue was also investigated. The ulcer index, lipid peroxidation and antioxidant enzyme activity (GPx, catalase, SOD) were determined. Pretreatment with garlic oil in doses of 0.25 and 0.5 mg/kg, 30 min before administration of ethanol (1 mL of 100%) caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 19 publications
2
16
0
1
Order By: Relevance
“…Animals of the third group were given a single nicorandil (Torrent Pharmaceuticals, India) dose (10 mg/kg), intraperitoneally [25], 30 min before a single indomethacin dose as in group two. The fourth group animals were given a single oral ethanol 100% (Prolabo) dose as 1 ml/100 g [19]. The fifth group animals were given a single nicorandil dose, 30 min before a single ethanol dose.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals of the third group were given a single nicorandil (Torrent Pharmaceuticals, India) dose (10 mg/kg), intraperitoneally [25], 30 min before a single indomethacin dose as in group two. The fourth group animals were given a single oral ethanol 100% (Prolabo) dose as 1 ml/100 g [19]. The fifth group animals were given a single nicorandil dose, 30 min before a single ethanol dose.…”
Section: Methodsmentioning
confidence: 99%
“…It causes mucosal cellular injury through activation of matrix metalloproteinase enzymes, TNF-α release, lipid peroxidation, and protein carbonyl formation [18]. Thus, ethanol was frequently used as an experimental inducer of acute gastric ulcers [19].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study preteatment of ethanol-induced gastic ulcer with garlic oil reduced the ulcer index and LPO and ameliorated the decrease in levels of antioxidant enzymes such as GPX, CAT, and SOD [43]. Aged garlic extract and diallyl polysulfides inhibit the formation of thiobarbituric acidreactive and fluorescent substances induced by iron-ascorbic acid in isolated liver microsomal membranes, indicating the protective effect of garlic against lipid peroxidation [44].…”
Section: Discussionmentioning
confidence: 97%
“…Gastric ulcers are also associated with increased lipid peroxidation [47][48][49][50][51][52]. It has been demonstrated that many pathologic conditions that caused elevation of MDA due to lipid peroxidation were prevented by carnitine and its derivatives, including ischemia/reperfusion injury [53][54][55], drug-induced cardiomyopathy [56][57][58], and myocardial infarction [59,60].…”
Section: Discussionmentioning
confidence: 99%